Learning in small firms across European rural regions, in Panagopoulos - Cesário, M. (2013)
Small medium enterprises (SMEs) interact intensely with the territory in which they locate. Is it possible to awake the need for innovation in SMEs and use them as incubators for local development? If so, how do firms behave when they are innovative? Which determinants have a more effective impact on the innovative choices of small firms? The present empirical analyses uses a set of enquires developed within the frame work of an European research project whose main goal was to model the determinants of innovation in a biunivocal relationship of interdependencies between small firms and their environmental contexts. We dealt mainly with lagging regions and the questionnaires were used in 323 firms located in 12 different European rural regions of six countries. The quantitative approach used demonstrated the level of proximity between innovation and firms choices related to factors like: formation of the leadership, or labour skills, coordinationa with suppliers and clients, realtionships with research institutions, external connections.